(untitled) (Praxis Educativa, 2025)
This paper aims to analyze public policy on Indigenous education in the state of Baja California, using Frantz Fanon’s epistemic approaches. Using a hermeneutic-dialectical method, which is supported by a qualitative approach, we use documentary review strategies to analyze the government’s public policy on Indigenous education for the 2019-2023 period. As a result, we report the process of amending Articles 31, 32, and 33 of the Education Law of the State of Baja California, as a result of the unconstitutionality claim issued by the National Human Rights Commission and the Supreme Court of Justice of the Nation. This ruling forced the state Congress and the state government to implement consultation forums among Indigenous peoples to guarantee the exercise of their rights in education, culture, and language. Finally, in the conclusions, we propose building public policy on education from critical decolonial epistemic matrices that incorporate the diversity of worldviews and knowledge to respond to, respect, and listen to all perspectives, both from uniqueness and differences.